Drug misuse in a special clinic patient population in Glasgow. Issue 5 (October 1976) - Bindemann, S; Wells, B W; Fish, F; Schofield, C B
Abstract : During the period October, 1970, to October, 1972, a sample of 295 patients attending Special Clinics in the City of Glasgow participated in an investigation into drug misuse. Results show that, of the 136 males and 159 females who took part--all within an age range of 16 to 24 years, 43 per cent. of the males and 36 per cent. of the females admitted to having experimented with drugs. These percentage figures on the prevalence of drug misuse compare with 36 per cent. of males and 24 per cent. of females obtained from other Glasgow-domiciled target groups, comprising a sample of 2, 514 individuals. The principal drug of misuse is shown to be cannabis, followed by LSD and sleeping pills. Data on drug availability suggest that little difficulty is experienced in obtaining drugs illicitly from a variety of sources. Comparison between drug misusers and non-misusers on domestic, educational, and social variables revealed no very distinctive patterns. Results of screening for personality characteristics, using Eysenck's Psychoticism, Extraversion and Neuroticism Inventory generally confirmed previous findings related to atypical scores on the P, E, and N parameters. Even so, results obtained by means of the PEN Inventory and IPAT Anxiety Scale revealed a pattern in which drug misuse is shown to be related to even higher scores of psychoticism, neuroticism, and anxiety. The results of the investigation are discussed with particular reference to the nature of the appeal of drugs to the sexually permissive and promiscuous.